KONSTRUKSI PENAFSIRAN YUNAHAR ILYAS (Studi Buku Kisah Para Rasul Tafsir Al-Qur’an Tematis) - Afifatur Rasyidah Insan N.A.; Muhammad Chirzin (Taqaddumi: Journal of Quran and Hadith Studies, 2021)
Understanding the construction of interpretation is important in helping to understand the interpretation of the Koran from someone creation, and for understanding the messages of the Koran. Likewise, understanding the construction of interpretation is very important to understand the stories in the Koran, so that humans can get wisdom and moral messages after contemplating the events narrated. Kisah Para Rasul Tafsir al-Qur’an Tematis is Yunahar Ilyas’ creation, as a moslem scholar. This creation has peculiarity, in sources aspect, methods, and his construction of interpretation. Yunahar Ilyas's interpretive construction consists of aspects which include the method of interpretation and the steps of interpretation. The interpretation method applied by Yunahar Ilyas is the maudhui method with a hermeneutic approach. The book of Acts of the Apostles Tafsir al-Qur’an Thematic has relevance to the contemporary context, namely having a contribution in scientific interpretation, educational value, and as da'wah for the community. The advantages of this thematic interpretation are that it is quite informative, concise, the language is easy to understand, and has clear sources. The drawbacks are not often discussing literature, lack of correlation with scientific knowledge, and on the story of the Prophet Muhammad that the discussion isn't over yet.